Alkaline electrolytic water hydrogen evolution reaction catalyst and preparation method thereof

CN122879749APending Publication Date: 2026-10-09NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611098037.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本申请提供一种碱性电解水析氢反应催化剂及其制备方法,旨在解决现有过渡金属磷化物HER催化剂基底附着力差、大电流密度下催化活性及稳定性差的技术问题

Benefits of technology

1.过渡金属磷化物催化剂与金属基底具有优异的界面结合力

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879749A_ABST
    Figure CN122879749A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of water electrolysis catalysts, in particular to an alkaline water electrolysis hydrogen evolution reaction catalyst and a preparation method thereof. The preparation method comprises the following steps: dissolving a zinc salt and a transition metal salt in water, then adding a pH buffer and a complexing agent to obtain a deposition solution; then depositing an alloy of zinc and a transition metal on a metal substrate through an electrodeposition method; immersing the metal substrate after electrodeposition in an alkaline solution for dealloying-self-corrosion treatment to obtain a precursor; and performing phosphorization treatment on the precursor by using phosphine to obtain the alkaline water electrolysis hydrogen evolution reaction catalyst. The hydroxide layer synthesized by the dealloying-self-corrosion method grows in situ from a metal, the compact hydroxide layer formed in situ is combined with the metal layer closely, so that the phosphorization layer obtained by the phosphorization treatment has strong interface bonding force with the substrate, and the prepared transition metal phosphide catalyst exhibits excellent catalytic activity and better stability in water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of water electrolysis catalyst technology, and in particular to an alkaline water electrolysis hydrogen evolution reaction catalyst and its preparation method. Background Technology

[0002] Alkaline water electrolysis is a key pathway for green hydrogen production, but its slow reaction kinetics limit the rate of hydrogen production, necessitating efficient catalysts to accelerate the reaction. Platinum and other noble metal-based catalysts, due to their near-zero binding energy with intermediate hydrogen, are considered the best-performing catalysts for the hydrogen evolution reaction (HER). However, the high cost and scarcity of noble metals limit their large-scale application. Transition metal phosphide catalysts, due to their excellent catalytic performance and stable chemical properties, are seen as alternatives to current noble metal catalysts and are receiving increasing attention; the preparation of high-performance, stable transition metal phosphide catalysts is of great significance for hydrogen production through water electrolysis.

[0003] Currently, the preparation of transition metal phosphide self-supported catalysts typically employs a solid-gas phase phosphating method. This involves first generating a transition metal hydroxide layer as a precursor on a metal substrate via hydrothermal or electrodeposition methods. Then, sodium hypophosphite is used as the phosphorus source, and the phosphine gas generated during the high-temperature decomposition of sodium hypophosphite phosphates the hydroxide layer into a phosphide layer. This method offers advantages such as simple synthesis, uniform gas-phase reaction, suitability for self-supported substrate loading, and large-scale preparation. However, the hydroxide layer synthesized by hydrothermal or electrodeposition methods is not grown in situ from the metal substrate, resulting in poor adhesion between the hydroxide layer and the substrate, which affects the interfacial bonding and stability of the phosphated phosphide layer with the substrate. Furthermore, to maximize the exposure of more catalytic active sites and thus enhance catalytic activity, current catalyst preparation often pursues large specific surface areas, layered structures, or porous structures. However, such complex surface structures further reduce the stability of the material. For example, ultrathin layered hydroxide structures synthesized by hydrothermal methods are prone to detachment during high current density testing, failing to meet industrial durability requirements.

[0004] Therefore, there is an urgent need to develop a transition metal phosphide catalyst that balances catalytic performance and durability, and is firmly aggregated and not easily detached at high current densities. Summary of the Invention

[0005] This application provides an alkaline water electrolysis hydrogen evolution reaction catalyst and its preparation method, aiming to solve the technical problems of poor substrate adhesion, poor catalytic activity and stability under high current density of existing transition metal phosphide HER catalysts.

[0006] To achieve the above objectives, the present application adopts the following technical solution.

[0007] The first aspect of this application provides a method for preparing a catalyst for an alkaline water electrolysis hydrogen evolution reaction, comprising the following steps: S1, zinc salt and transition metal salt are dissolved in water, and then pH buffer and complexing agent are added to obtain a deposition solution; then an alloy of zinc and transition metal is deposited on a metal substrate by electrodeposition. S2, the electrodeposited metal substrate is immersed in an alkaline solution for dealloying-self-corrosion treatment to obtain the precursor; S3, the precursor is phosphated with phosphine to obtain an alkaline water electrolysis hydrogen evolution reaction catalyst.

[0008] Preferably, the transition metal salt is at least one of a nickel salt or a cobalt salt; The pH buffer includes sodium acetate, ammonium chloride, and H3BO3; The complexing agent is sodium citrate; The metal substrate is nickel foam, nickel sheet, or nickel mesh; The alkaline solution is an aqueous solution of KOH.

[0009] More preferably, the zinc salt is zinc sulfate or zinc chloride; The nickel salt is nickel sulfate or nickel chloride; The cobalt salt is cobalt sulfate or cobalt chloride.

[0010] Preferably, the deposition of an alloy of zinc and transition metals on a metal substrate by electrodeposition specifically includes: A three-electrode system was assembled with a metal substrate as the cathode, a carbon rod as the anode, and a mercury / mercury oxide electrode as the reference electrode, and a deposition solution. The cathode is subjected to reduction potential deposition to deposit an alloy of zinc and transition metals on a metal substrate, thus obtaining the precursor.

[0011] Further preferably, the current density for reduction potential deposition is 0.1 A·cm. -2 The electrodeposition time is above 800 s.

[0012] Preferably, the dealloying-self-corrosion treatment is performed at room temperature for more than 24 hours.

[0013] Preferably, the phosphating treatment is performed at a temperature of 300-400 °C for a time of 2 hours or more.

[0014] Preferably, the concentration of zinc salt in the deposition solution is 0.05 mol·L⁻¹. -1 The concentration of the transition metal salt is 0.1 mol·L⁻¹. -1 The concentration of the pH buffer is 0.45 mol·L⁻¹. -1 The concentration of the complexing agent is 1 mol·L⁻¹ -1 .

[0015] More preferably, the molar ratio of sodium acetate, ammonium chloride and H3BO3 in the pH buffer is 1:2:1.5.

[0016] A second aspect of this application provides an alkaline water electrolysis hydrogen evolution reaction catalyst prepared by the above-described preparation method.

[0017] Compared with the prior art, the beneficial effects of this application are as follows: 1. Transition metal phosphide catalysts exhibit excellent interfacial bonding with metal substrates. The hydroxide layer synthesized in this application using a dealloying-self-corrosion method is formed by in-situ growth of the metal. The dense hydroxide layer formed by in-situ growth is tightly bonded to the metal layer, thereby giving the phosphating layer obtained by phosphating treatment a strong interfacial bond with the substrate.

[0018] 2. Transition metal phosphide catalysts exhibit excellent catalytic activity in water electrolysis; The dissolution of zinc during the dealloying-self-corrosion process generates a large number of pores, significantly increasing the material's specific surface area. The high specific surface area material maintains its porous morphology after phosphating, thus possessing a large number of metal-phosphorus catalytic active sites, significantly improving its catalytic performance, while avoiding the structural strength deficiency typically faced by porous structures.

[0019] 3. Transition metal phosphide catalysts exhibit better stability at high current densities. Compared to traditional hydrothermal or electrodeposition methods for hydroxide layers, the hydroxide layer grown in situ from the metal substrate by self-corrosion in this application is tightly bonded to the substrate, making the prepared phosphating layer less prone to detachment, able to withstand bubble impacts at higher current densities, and exhibiting excellent stability. Attached Figure Description

[0020] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 Here is a SEM image of the transition metal phosphide catalyst from Example 1; Figure 2 This is a surface EDS mapping diagram of the transition metal phosphide catalyst in Example 1; Figure 3 EDS diagram of the transition metal phosphide catalyst in Example 1; Figure 4The XRD pattern of the transition metal phosphide catalyst in Example 1 is shown below. Figure 5 LSV curves of the catalysts in the examples and comparative examples; Figure 6 The graph shows the chronopotential stability test results of the transition metal phosphide catalysts in Example 1 and Comparative Example 5. Detailed Implementation

[0022] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0023] In the following description of this embodiment, the terms "including", "comprising", "having", and "containing" are all open-ended terms, meaning that they include but are not limited to.

[0024] In the following description of this embodiment, the term "and / or" is used to describe the association relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, B existing alone, and A and B existing simultaneously. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0025] In the following description of this embodiment, the term "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0026] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0027] Those skilled in the art should understand that, in the following description of the embodiments of this application, the sequence of numbers does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0028] Those skilled in the art will understand that the numerical ranges in the embodiments of this application should be understood as each intermediate value between the upper and lower limits of the specifically disclosed range. Each smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this application. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0029] Unless otherwise stated, the technical / scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. While this application describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this application. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0030] This application provides a method for preparing an alkaline water electrolysis hydrogen evolution reaction catalyst. The method involves growing a precursor on a metal substrate using a dealloying-self-corrosion method, followed by high-temperature solid-gas phase phosphating to obtain a transition metal phosphide catalyst, i.e., an alkaline water electrolysis hydrogen evolution reaction catalyst. Specifically, the method includes the following steps: S1, zinc salt and transition metal salt are dissolved in water, and then pH buffer and complexing agent are added to obtain a deposition solution; then an alloy of zinc and transition metal is deposited on a metal substrate by electrodeposition. In this application, the transition metal is at least one of nickel or cobalt, and the transition metal salt is a nickel salt and / or a cobalt salt.

[0031] The nickel salt is selected from nickel sulfate or nickel chloride; the cobalt salt is selected from cobalt sulfate or cobalt chloride.

[0032] The zinc salt is selected from zinc sulfate or zinc chloride.

[0033] The pH buffer comprises sodium acetate, ammonium chloride and H3BO3, wherein the molar ratio of sodium acetate, ammonium chloride and H3BO3 is preferably 1:2:1.5.

[0034] The complexing agent is sodium citrate.

[0035] In the precipitation solution prepared in this application, the concentration of zinc salt is 0.05 mol·L⁻¹. -1 The concentration of the transition metal salt is 0.1 mol·L⁻¹. -1 The concentration of the pH buffer is 0.45 mol·L⁻¹. -1 The concentration of the complexing agent is 1 mol·L⁻¹ -1 .

[0036] In this application, the deposition of an alloy of zinc and transition metals on a metal substrate by electrodeposition specifically includes: A three-electrode system was assembled with a metal substrate as the cathode, a carbon rod as the anode, and a mercury / mercury oxide electrode as the reference electrode, and a deposition solution. The cathode is subjected to reduction potential deposition to deposit an alloy of zinc and transition metals on a metal substrate, thus obtaining the precursor.

[0037] In this application, the metal substrate is nickel foam, nickel sheet, or nickel mesh, and a nickel-cobalt-zinc alloy layer is deposited on the metal substrate by electrodeposition. The current density for reduction potential deposition should be at least 0.1 A·cm⁻¹. -2 The preferred value is 0.1 A·cm. -2 The electrodeposition time is 800 s or more, preferably 800 s.

[0038] S2, the electrodeposited metal substrate is immersed in an alkaline solution for dealloying-self-corrosion treatment to obtain the precursor; In this application, the alkaline solution is an aqueous solution of KOH. Specifically, the electrodeposited metal substrate is immersed in a 1 mol·L⁻¹ solution. -1 In KOH solution, zinc dissolves naturally to form a porous, easily corroded nickel-cobalt layer. The ambient temperature is maintained at room temperature, and the solution is soaked for 24 hours to allow the porous transition metal to be fully corroded, resulting in a precursor with a porous surface and a dense hydroxide layer.

[0039] S3, the precursor is phosphated with phosphine to obtain an alkaline water electrolysis hydrogen evolution reaction catalyst.

[0040] In this application, the phosphating treatment is carried out at a temperature of 300-400 ℃, preferably 350 ℃, for a time of 2 hours or more, preferably 2 hours.

[0041] Specifically, the precursor is placed downstream of a tube furnace, and sodium hypophosphite is placed upstream as the phosphorus source. Under an argon atmosphere, the temperature is increased from room temperature to 350 °C within 30 minutes, causing the sodium hypophosphite to decompose and produce phosphine. The precursor is maintained at 350 °C for 2 hours for complete phosphating. After cooling to room temperature, the downstream product is removed to obtain the transition metal phosphide catalyst, which is the catalyst for the alkaline water electrolysis hydrogen evolution reaction.

[0042] This application utilizes a dealloying-self-corrosion method to synthesize a transition metal phosphide catalyst, in which the hydroxide layer is formed by in-situ growth of the metal. The dense hydroxide layer formed by in-situ growth is tightly bonded to the metal layer, thereby giving the phosphating layer obtained through phosphating treatment a strong interfacial bond with the substrate.

[0043] The transition metal phosphide catalyst prepared in this application, namely the alkaline water electrolysis hydrogen evolution reaction catalyst, exhibits excellent catalytic activity and stability. Due to the dissolution of zinc during the dealloying-self-corrosion process, a large number of pores are generated, significantly increasing the specific surface area of ​​the transition metal phosphide catalyst. This high specific surface area maintains its porous morphology after phosphating, thus possessing a large number of metal-phosphorus catalytic active sites, significantly improving its catalytic performance, while avoiding the structural strength deficiency typically faced by porous structures.

[0044] Compared to traditional hydrothermal or electrodeposition methods for hydroxide layers, the hydroxide layer grown in situ from the metal substrate by self-corrosion in this application is tightly bonded to the substrate, making the prepared phosphating layer less prone to detachment, able to withstand bubble impacts at higher current densities, and exhibiting excellent stability.

[0045] The present application will be further described below through specific embodiments.

[0046] Example 1 This embodiment provides a nickel-cobalt phosphide catalyst, the preparation method of which includes: S1. Add zinc sulfate (analytical grade), nickel sulfate (99% or higher purity), cobalt sulfate (99% or higher purity), sodium acetate (99% or higher purity), ammonium chloride (99.5% purity), boric acid (99% or higher purity), and sodium citrate (95% or higher purity) to deionized water and stir until completely dissolved to prepare the precipitation solution.

[0047] The concentrations of each component in the sediment were as follows: zinc sulfate 0.05 mol·L⁻¹ -1 Nickel sulfate 0.1 mol·L -1 0.1 mol·L⁻¹ cobalt sulfate -1 Sodium acetate 0.1 mol·L -1 ammonium chloride 0.2 mol·L -1 Boric acid 0.15 mol·L -1 Sodium citrate 1 mol·L -1 .

[0048] The nickel foam substrate was rinsed with hydrochloric acid and deionized water, respectively, and used as the cathode. A three-electrode system was constructed using a carbon rod as the anode and a mercury / mercury oxide electrode as the reference electrode. The deposition solution was filled at a flow rate of 0.1 A·cm⁻¹. -2 The cathode was subjected to reduction potential deposition at a current density of 800 s, and a foamed nickel substrate with nickel-cobalt-zinc alloy deposited on the surface was obtained.

[0049] S2, prepared using KOH with a purity of 95% or higher, yields 1 mol·L⁻¹ -1A nickel foam substrate with deposited nickel-cobalt-zinc alloy was immersed in a KOH solution at room temperature for 24 hours to allow for sufficient corrosion of the nickel-cobalt-zinc alloy. After 24 hours, the substrate was removed, washed with deionized water, and dried to obtain a self-supporting substrate, i.e., a precursor, with a nickel-cobalt hydroxide layer on its surface.

[0050] S3: The precursor is placed downstream of a tube furnace, and 0.6 g of sodium hypophosphite is placed upstream as the phosphorus source. Under an argon atmosphere, the temperature is increased from room temperature to 350 °C within half an hour to decompose the sodium hypophosphite and produce phosphine. The temperature is maintained at 350 °C for 2 hours to ensure complete phosphating. After cooling to room temperature, the transition metal phosphide catalyst is obtained.

[0051] Example 2 This embodiment provides a nickel phosphide catalyst, the preparation method of which includes: S1. Add zinc sulfate (analytical grade), nickel sulfate (purity ≥ 99%), sodium acetate (purity ≥ 99%), ammonium chloride (purity ≥ 99.5%), boric acid (purity ≥ 99%), and sodium citrate (purity ≥ 95%) to deionized water and stir until completely dissolved to prepare the precipitation solution.

[0052] The concentrations of each component in the sediment were as follows: zinc sulfate 0.05 mol·L⁻¹ -1 Nickel sulfate 0.1 mol·L -1 Sodium acetate 0.1 mol·L -1 ammonium chloride 0.2 mol·L -1 Boric acid 0.15 mol·L -1 Sodium citrate 1 mol·L -1 .

[0053] S2 is the same as in Example 1.

[0054] S3 is the same as in Example 1.

[0055] Example 3 This embodiment provides a cobalt phosphide catalyst, the preparation method of which includes: S1. Add zinc sulfate (analytical grade), cobalt sulfate (99% or higher purity), sodium acetate (99% or higher purity), ammonium chloride (99.5% purity), boric acid (99% or higher purity), and sodium citrate (95% or higher purity) to deionized water and stir until completely dissolved to prepare the sedimentation solution.

[0056] The concentrations of each component in the sediment were as follows: zinc sulfate 0.05 mol·L⁻¹ -1 0.1 mol·L⁻¹ cobalt sulfate -1 Sodium acetate 0.1 mol·L -1 ammonium chloride 0.2 mol·L-1 Boric acid 0.15 mol·L -1 Sodium citrate 1 mol·L -1 .

[0057] S2 is the same as in Example 1.

[0058] S3 is the same as in Example 1.

[0059] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step S3 was omitted, i.e., no phosphating treatment was performed; all other aspects are the same as in Example 1.

[0060] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that step S3 was omitted, i.e., no phosphating treatment was performed; the rest were the same as Example 2.

[0061] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that step S3 was omitted, i.e., no phosphating treatment was performed; all other aspects are the same as Example 3.

[0062] Comparative Example 4 The commercial nickel foam was rinsed sequentially with hydrochloric acid and deionized water.

[0063] Comparative Example 5 This comparative example provides a nickel-cobalt phosphide catalyst prepared using a conventional hydrothermal-phosphating method, the specific preparation method of which includes: S1. 1 mmol of nickel nitrate (98% purity or higher), 1 mmol of cobalt nitrate (99% purity or higher), and 10 mmol of urea (99.5% purity or higher) were added to a beaker, along with 40 mL of deionized water and stirred thoroughly. The well-mixed solution and nickel foam were transferred to a polytetrafluoroethylene (PTFE) reactor and heated at 160 °C for 10 hours. After cooling, the nickel foam was removed, washed with deionized water and ethanol, and dried to obtain a self-supporting substrate, i.e., the precursor, with a nickel-cobalt hydroxide layer on its surface.

[0064] S2: The precursor is placed downstream of a tube furnace, and 0.6 g of sodium hypophosphite is placed upstream as the phosphorus source. Under an argon atmosphere, the temperature is raised from room temperature to 350 °C within half an hour to decompose the sodium hypophosphite and produce phosphine. The temperature is maintained at 350 °C for 2 hours to ensure complete phosphating. After cooling to room temperature, the nickel-cobalt phosphide catalyst is obtained.

[0065] The catalysts prepared in Example 1 and the comparative example were subjected to microstructure testing and performance evaluation, as detailed below: 1. Microstructure and composition analysis The nickel-cobalt phosphide catalyst prepared in Example 1 was subjected to SEM, surface EDS, and XRD tests, and the results are as follows: Figures 1-4 As shown.

[0066] Figure 1 Its SEM spectrum, from Figure 1 It can be seen that the material surface has a porous morphology.

[0067] Figure 2 Its EDS mapping spectrum, from Figure 2 It can be seen that the elemental composition of the material surface is mainly nickel, cobalt and phosphorus, and the distribution is that the cobalt phosphide is embedded in the nickel phosphide in a lamellar form.

[0068] Figure 3 Its EDS plot, from Figure 3 The material has high nickel, cobalt, and phosphorus content, but low zinc content, which confirms the successful dissolution of zinc in the previous dealloying-self-corrosion step.

[0069] Figure 4 Its XRD pattern, from Figure 4 It can be seen that the material contains Ni2P and Ni 12 P5, as a component, confirms the successful synthesis of nickel phosphide.

[0070] 2. Electrochemical performance testing Electrochemical tests were performed on the catalysts in the embodiments and comparative examples of this application using a three-electrode system, with the above-mentioned catalyst as the working electrode, the mercury / mercury oxide electrode as the reference electrode, and the carbon rod electrode as the counter electrode.

[0071] To evaluate the hydrogen evolution activity of the catalyst, LSV curves were performed at a scan rate of 10 mV·s. -1 The test results are as follows: Figure 5 As shown.

[0072] from Figure 5 It can be seen that the nickel-cobalt phosphide catalyst of Example 1 has a performance of 10 mA·cm⁻¹ 2 The overpotential at that time was 77.1 mV, and the Tafel slope was only 48.59 mV·dec. -1 The nickel phosphide catalyst in Example 2 was tested at 10 mA·cm⁻¹. 2 The overpotential at that time was 104.6 mV, and the Tafel slope was only 62.92 mV·dec. -1 The cobalt phosphide catalyst in Example 3 was tested at 10 mA·cm⁻¹. 2 The overpotential at that time was 88.8 mV, and the Tafel slope was only 58.43 mV·dec. -1 .

[0073] For comparison, Comparative Example 1 was at 10 mA·cm 2 The overpotential at time 145 mV was compared to that at 10 mA·cm⁻¹ in Comparative Example 2. 2 The overpotential at that time was 107 mV, and that of Comparative Example 3 at 10 mA·cm 2 The overpotential at 10 mA·cm⁻¹ was 156 mV; Comparative Example 4 had an overpotential of 156 mV at 10 mA·cm⁻¹. 2 The overpotential at that time was 250 mV.

[0074] The LSV curve test data shows that the material possesses excellent HER catalytic performance. The examples and comparative examples demonstrate that the phosphated material exhibits significantly improved performance compared to the unphosphated material, confirming the synergistic effect of the transition metal-phosphorus binding on HER performance. Example 1 and Comparative Example 1 show that the nickel-cobalt bonded product significantly improves the HER performance of the material compared to a single metal material, validating the significance of selecting nickel and cobalt as constituent elements of the materials in this application.

[0075] To evaluate the operational stability of the catalysts, chronopotential stability tests were performed on the nickel-cobalt phosphide catalyst of Example 1 and the catalyst prepared by the conventional hydrothermal-phosphating method in Comparative Example 5. The results are as follows: Figure 6 As shown.

[0076] Test results show that the nickel-cobalt phosphide catalyst of Example 1 performs well at a temperature of 25 °C and an electrolyte concentration of 1 mol·L⁻¹. - 1 KOH, operating current is 500 mA·cm -2 Under the specified conditions, the self-supporting phosphide catalyst prepared in this application can operate stably for about 350 hours, demonstrating excellent stability and indicating strong adhesion of the catalyst to the substrate. In contrast, the catalyst of Comparative Example 5, prepared using the hydrothermal method, detaches within hours, leading to performance degradation and inability to operate stably for a long period.

[0077] Although this application has been described in detail in this specification with general descriptions and specific embodiments, some modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, such modifications or improvements made without departing from the spirit of this application are all within the scope of protection claimed in this application.

Claims

1. A method for preparing an alkaline water electrolysis hydrogen evolution reaction catalyst, characterized in that, Includes the following steps: S1, zinc salt and transition metal salt are dissolved in water, and then pH buffer and complexing agent are added to obtain a deposition solution; then an alloy of zinc and transition metal is deposited on a metal substrate by electrodeposition. S2, the electrodeposited metal substrate is immersed in an alkaline solution for dealloying-self-corrosion treatment to obtain the precursor; S3, the precursor is phosphated with phosphine to obtain an alkaline water electrolysis hydrogen evolution reaction catalyst.

2. The preparation method according to claim 1, characterized in that, The transition metal salt is at least one of nickel salt or cobalt salt; The pH buffer includes sodium acetate, ammonium chloride, and H3BO3; The complexing agent is sodium citrate; The metal substrate is nickel foam, nickel sheet, or nickel mesh; The alkaline solution is an aqueous solution of KOH.

3. The preparation method according to claim 2, characterized in that, The zinc salt is zinc sulfate or zinc chloride; The nickel salt is nickel sulfate or nickel chloride; The cobalt salt is cobalt sulfate or cobalt chloride.

4. The preparation method according to claim 1, characterized in that, Depositing zinc and transition metal alloys on a metal substrate via electrodeposition, specifically including: A three-electrode system was assembled with a metal substrate as the cathode, a carbon rod as the anode, and a mercury / mercury oxide electrode as the reference electrode, and a deposition solution. The cathode is subjected to reduction potential deposition to deposit an alloy of zinc and transition metals on a metal substrate, thus obtaining the precursor.

5. The preparation method according to claim 4, characterized in that, The current density for reduction potential deposition is 0.1 A·cm. -2 The electrodeposition time is above 800 s.

6. The preparation method according to claim 1, characterized in that, The dealloying-self-corrosion treatment is performed at room temperature for more than 24 hours.

7. The preparation method according to claim 1, characterized in that, The phosphating treatment is carried out at a temperature of 300-400 ℃ for a time of more than 2 hours.

8. The preparation method according to claim 1, characterized in that, The concentration of zinc salt in the sediment is 0.05 mol·L⁻¹. -1 The concentration of the transition metal salt is 0.1 mol·L⁻¹. -1 The concentration of the pH buffer is 0.45 mol·L⁻¹. -1 The concentration of the complexing agent is 1 mol·L⁻¹ -1 .

9. The preparation method according to claim 8, characterized in that, The molar ratio of sodium acetate, ammonium chloride, and H3BO3 in the pH buffer is 1:2:1.

5.

10. The alkaline water electrolysis hydrogen evolution reaction catalyst prepared by the preparation method according to any one of claims 1-9.